Postoperative astigmatism after small-incision cataract surgery with sclera tunnel suturing and without scleral tunnel suturing: A comparative study - Mohammed S Ahmed (Journal of Medicine in Scientific Research, 2021)
Background and aim Cataract represents a significant socioeconomic burden and a public health concern, as it is the leading cause of blindness worldwide. Small-incision cataract surgery (SICS) is one of the cataract surgical techniques commonly used in developing countries. There have been many improvements and changes in SICS's technique since its development, including changes in the site and size of the incision. Patients and methods This study was conducted aiming to study postoperative astigmatism after SICS with or without scleral tunnel suturing. This study was performed on 100 eligible eyes in 59 consecutive patients. Identical surgical methods were used in all cases except for wound closure technique as patients were allocated into two groups, where SICS was performed with scleral tunnel suturing in the group A and without scleral tunnel suturing in the group B. Patients were assessed preoperatively and were followed up for 3 months. Results and conclusion The study revealed a highly statistically improvement in visual acuity at 3 months postoperatively in both groups. Meanwhile, SICS performed either with or without scleral tunnel suturing was not associated with significant preoperative and postoperative astigmatism changes. In addition, in terms of postoperative visual acuity or refraction, no statistically significant differences were observed between the two classes. Therefore, according to anterior chamber's stability and close closure of the scleral tunnel and conjunctival wounds, it is a case-specific situation and acceptable for each case.